The UVX quasar optical luminosity function and its evolution - Goldschmidt, P; Miller, L (1997)
The recently-finished Edinburgh UVX quasar survey at B < 18 is used together with other complete samples to estimate the shape and evolution of the optical luminosity function in the redshift range 0.3 < z < 2.2. There is a significantly higher space density of quasars at high luminosity and low redshift than previously found in the PG sample of Schmidt and Green (1983), with the result that the shape of the luminosity function at low redshifts (z < 1) is seen to be consistent with a single power-law. At higher redshifts the slope of the power-law at high luminosities appears to steepen significantly. There does not appear to be any consistent break feature which could be used as a tracer of luminosity evolution in the population.